Thermally stable cellulose nanospheres prepared from office waste paper by complete removal of hydrolyzed sulfate groups. (1st December 2022) - Lam, Duc-Ninh; Thien, Doan Van Hong; Nguyen, Chanh-Nghiem; Nguyen, Nhung Tuyet Thi; Van Viet, Nguyen; Van-Pham, Dan-Thuy
Abstract: Cellulose nanocrystals are commonly obtained by acid hydrolysis, particularly with H2 SO4 . However, a small amount of deposited sulfate-groups contributes to the degradation of their thermal stability. This study prepared thermally-stable and sulfate-group-free cellulose nanospheres (CNSs) from office waste paper by H2 SO4 hydrolysis followed by solvolytic desulfation. The optimal desulfation conditions (i.e., 5 wt% MeOH, reaction temperature of 90 °C, a reaction time of 20 min, 0.5 mM pyridine) were preliminarily found from a one-factor-at-a-time experiment and validated by the results of a central composite design. The optimal desulfation conditions promoted environmental sustainability with less pyridine and MeOH and comparably shorter reaction time. The desulfated CNSs had a significant thermal stability enhancement from 186 to 340 °C. Comprehensive characterization of the morphology, chemical composition, and thermal behavior of the desulfated CNSs reconfirmed the complete removal of sulfate groups without harmful pyridine residues, demonstrating the potential use of the thermally stable CNSs. Graphical abstract: Unlabelled Image Highlights: Cellulose nanospheres (CNSs) from office waste paper was produced by H2 SO4 hydrolysis. The solvolytic method was successfully applied to completely desulfate CNSs. The optimal desulfation conditions promoted environmental sustainability. Thermal stability of the desulfated CNSs was significantly enhanced.